1955
DOI: 10.1111/j.1365-2494.1955.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Strains of White Clover

Abstract: During the past few years much publicity has been given to the losses caused by bloat in cattle, and the suggestion has been made that the incidence of bloat has increased owing to the use in leys ofthe white clover S.IOO. To investigate this, observations on tendency to bloat were made on a series of experimental plots of S.IOO, S.IOO Nomark and S.184 white clovers, each sown in association with S.23 perennial ryegrass. The observations included a study of factors influencing the occurrence of bloat as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1959
1959
1981
1981

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…(1957) found no effects due to climate in their bloat trials. Troughton (1955) found no correlations between maximum and minimum temperatures, rainfall, sunshine, or humidity and the incidence of bloat. Barrentine (1959) found no basis for the belief that grazing dew-or rain-wet legumes causes bloat and suggested that most cases of critical bloat actually occur on clear warm days.…”
Section: Work By Ferguson (Cited By Maclay and Thompson In Colementioning
confidence: 79%
See 4 more Smart Citations
“…(1957) found no effects due to climate in their bloat trials. Troughton (1955) found no correlations between maximum and minimum temperatures, rainfall, sunshine, or humidity and the incidence of bloat. Barrentine (1959) found no basis for the belief that grazing dew-or rain-wet legumes causes bloat and suggested that most cases of critical bloat actually occur on clear warm days.…”
Section: Work By Ferguson (Cited By Maclay and Thompson In Colementioning
confidence: 79%
“…On the other hand, Troughton (1955) extrapolates from the work of another investigator with sudan grass in suggesting that increases of bloat noted on plots low in soil phosphate may have resulted from increased cyanide content of the clover forage consumed. Total intake of cyanide was correlated with bloat incidence.…”
Section: Foam Theorymentioning
confidence: 97%
See 3 more Smart Citations